2014
DOI: 10.2298/bah1404669p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary garlic addition on productive performance and blood lipid profile of broiler chickens

Abstract: The aim of this study was to investigate the effect of dietary garlic powder addition on productive performance and blood lipid status of broiler chicken. At the beginning of experiment, three treatments of 150 one day old broiler chickens of hybrid line Hubbard per treatment, on a total of 450 chickens were formed. Every treatment was divided in four groups which represents four replicates of the experiment. Control treatment (T1) was fed with mixtures without addition of garlic powder, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 11 publications
5
23
1
Order By: Relevance
“…No differences on serum cholesterol levels observed also Bampidis et al (2005) and Sarica et al (2005) who evaluated the effect of dietary supplementation with oregano oil. In contrast to present study, decreasing effect of phytoadditives on serum triglycerides level recorded Puvača et al (2015) and Rahimi et al (2011). Abou-Elkhair et al (2014) researched bioactive effect of dietary supplementation with essential oils blends of oregano, thyme and garlic on blood parameters of broilers.…”
Section: Blood Parameters Of Laying Henscontrasting
confidence: 99%
“…No differences on serum cholesterol levels observed also Bampidis et al (2005) and Sarica et al (2005) who evaluated the effect of dietary supplementation with oregano oil. In contrast to present study, decreasing effect of phytoadditives on serum triglycerides level recorded Puvača et al (2015) and Rahimi et al (2011). Abou-Elkhair et al (2014) researched bioactive effect of dietary supplementation with essential oils blends of oregano, thyme and garlic on blood parameters of broilers.…”
Section: Blood Parameters Of Laying Henscontrasting
confidence: 99%
“…Moreover, the conducted analysis showed only slightly higher (P > 0.05) concentration of triglycerides in turkeys of control group compare to birds from experimental group. The decreasing effect of phytoadditives on serum triglycerides level observed also Abou-elkhair, et al (2014), Gerzilov, et al (2011), Puvača, et al (2015, Rahimi, et al (2011) andSaki, et al (2014). Have been suggested that the lower serum concentrations of triglycerides and cholesterol in birds who received phytogenic feed additive could be related to the complex antistress, antioxidant and antimicrobial effect of herbs included in the feed supplement.…”
Section: Resultsmentioning
confidence: 69%
“…In parallel, Puvača et al [31] postulated that adding black pepper to broiler diets has a positive impact on growth rate of chickens; this is in accordance with the antecedent studies of Al-Kassie et al [22] and Valiollahi et al [32]. Additionally, Abou-Elkhair et al [33] showed that the addition of black pepper, or a mixture of turmeric powder and black pepper, to broiler chicken diets led to a higher final body weight of chickens during the fattening period of 35 days.…”
Section: Discussionmentioning
confidence: 99%